Complete response of a metastatic microsatellite-stable gastric cancer after neoadjuvant chemoimmunotherapy: should we still operate? A case report and review of the literature - Mechahougui, Hiba; Chevallay, Mickael; Cauchy, François; Chaveau, Nicolas; Puppa, Giacomo; Koessler, Thibaud; Monig, Stefan (Frontiers in Oncology, 2024)
Gastric cancer often presents at an advanced stage in Western populations due to a lack of screening programs, leading to poor prognoses. Historically, palliative chemotherapy resulted in a median survival of 9.9 months. However, the introduction of the FLOT regimen and immunotherapy has significantly altered treatment outcomes. Oligometastatic gastric cancer, defined as metastasis limited to a single organ or a few sites, has emerged as a distinct subgroup with improved survival when treated with a combination of systemic and local therapies. We present the case of a 54-year-old male patient diagnosed with microsatellite-stable (MSS) oligometastatic gastric adenocarcinoma, including liver and peritoneal metastases, who achieved a complete pathological response following neoadjuvant chemoimmunotherapy with FOLFOX and nivolumab. Despite unfavorable prognostic factors, such as liver involvement and positive peritoneal cytology, the patient responded well to the treatment, allowing curative surgery. Postoperative histology confirmed complete regression of both the primary tumor and metastases, with no recurrence observed at the 1-year follow-up. This case shows the potential of combined chemoimmunotherapy to convert previously inoperable MSS gastric cancer to surgical candidates. Further research is needed to better define patient selection criteria and assess long-term outcomes for these patients.